2008
DOI: 10.1152/ajpgi.90202.2008
|View full text |Cite
|
Sign up to set email alerts
|

Candidate genes and sensory functions in health and irritable bowel syndrome

Abstract: Zinsmeister AR. Candidate genes and sensory functions in health and irritable bowel syndrome. Am J Physiol Gastrointest Liver Physiol 295: 219 -225, 2008. First published May 29, 2008 doi:10.1152/ajpgi.90202.2008.-Adrenergic and serotonergic (ADR-SER) mechanisms alter gut (GI) function; these effects are mediated through G protein transduction. Candidate genetic variations in ADR-SER were significantly associated with somatic scores in irritable bowel syndrome (IBS) and gastric emptying but not small bowel o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 49 publications
6
42
1
3
Order By: Relevance
“…Our data showed that C-1291G polymorphism in ADRA2A was not different in the patient and control groups, so there was no significant association between ADRA2A C-1291G polymorphism and IBS in Turkish population. Our results were similar to those of Camilleri, that he could not detect any relation between α2A genotype and subtypes of IBS (14). The high number of C-IBS and very low number of D-IBS patients might be the reason for statistical nonsignificance since ADRA2A is found to be responsible for mediating intestinal antisecretory action and probably is involved in pathogenesis of D-IBS (15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 87%
“…Our data showed that C-1291G polymorphism in ADRA2A was not different in the patient and control groups, so there was no significant association between ADRA2A C-1291G polymorphism and IBS in Turkish population. Our results were similar to those of Camilleri, that he could not detect any relation between α2A genotype and subtypes of IBS (14). The high number of C-IBS and very low number of D-IBS patients might be the reason for statistical nonsignificance since ADRA2A is found to be responsible for mediating intestinal antisecretory action and probably is involved in pathogenesis of D-IBS (15)(16)(17)(18)(19).…”
Section: Discussionsupporting
confidence: 87%
“…82 5-HTTLPR LS/SS genotype is also associated with both increased pain sensation and increased rectal compliance. 83 Serotonin is produced in the GI tract, brain, and neuronal cells, and is involved in GI motility and sensation. SERT regulates the amount of serotonin, and the S/S allele is associated with lower expression of SERT than the L/L allele, with serotonin absorption being half that of the L/L allele.…”
Section: Genetics and Early Life Eventsmentioning
confidence: 99%
“…The 5-HTTLPR genotype (S allele) is associated with higher pain sensory ratings during rectal distension studies in health and IBS, and the increased sensation ratings in carriers of the S allele are not caused by lower rectal compliance (19).…”
Section: Neurotransmitter Mechanismsmentioning
confidence: 99%